2016
DOI: 10.1002/nbm.3510
|View full text |Cite
|
Sign up to set email alerts
|

Information‐based ranking of 10 compartment models of diffusion‐weighted signal attenuation in fixed prostate tissue

Abstract: This study compares the theoretical information content of single‐ and multi‐compartment models of diffusion‐weighted signal attenuation in prostate tissue. Diffusion‐weighted imaging (DWI) was performed at 9.4 T with multiple diffusion times and an extended range of b values in four whole formalin‐fixed prostates. Ten models, including different combinations of isotropic, anisotropic and restricted components, were tested. Models were ranked using the Akaike information criterion. In all four prostates, two‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 32 publications
5
26
1
Order By: Relevance
“…The model that best explains the data varies in different tumours and regions, which is not unexpected given the diversity of breast cancer microstructure. This variation has also been reported in ex vivo prostate studies . A small fraction of voxels were excluded from fitting as a result of non‐mono‐exponential T 2 decay, and histology revealed that many such voxels were in necrotic regions.…”
Section: Discussionsupporting
confidence: 63%
“…The model that best explains the data varies in different tumours and regions, which is not unexpected given the diversity of breast cancer microstructure. This variation has also been reported in ex vivo prostate studies . A small fraction of voxels were excluded from fitting as a result of non‐mono‐exponential T 2 decay, and histology revealed that many such voxels were in necrotic regions.…”
Section: Discussionsupporting
confidence: 63%
“…As the acinal and epithelial water diffusion is essentially isotropic , variations in anisotropy reflecting stromal tissue changes may be masked or attenuated in voxels of the typical volume used in vivo. This possibility is supported by a recent comparison of seven compartment models of diffusion in (fixed) prostate tissue which found that a two‐compartment model comprising one isotropic and one anisotropic component was the best descriptor of the DWI signal attenuation over a range of diffusion times . It is possible that potentially diagnostic diffusion anisotropy changes are present, but not detectable by the simple monoexponential DTI method due to “masking” by a significant isotropic signal.…”
Section: Discussionmentioning
confidence: 94%
“…In the first VERDICT framework, the ICS and ECS diffusivities were fixed based on fit optimization performed on preliminary data [16], and found consistent with values derived from ex vivo studies with high SNR [57]. To further improve the fit robustness, the pseudo-diffusion coefficient of the water inside blood vessels was also fixed when characterizing prostatic tissue lesions in vivo in a later study [49].…”
Section: Fixing Parametersmentioning
confidence: 99%
“…Tissue lesions are often considered isotropic for convenience and practicality [49], potentially at the expense of specificity [57].…”
Section: Time and Hardware Issues Acquisition Timementioning
confidence: 99%